Analisis Usaha Pengolahan Tembakau Aspen di Desa Wonosari Kecamatan Trucuk Kabupaten Klaten - Daru Retnowati; Yulianto Yulianto; Vini Arumsari (Jurnal Dinamika Sosial Ekonomi, 2009)
Mount the farmer earnings most coming from result from that yield up the ghost Agriculture very required in sustaining life one day represent one of agricultural produce and represent the economics activity Where com pany smoke very of raw material tabacco to be made a product become in the form of cigarette This reasearch aim to to analyse the level of storey lavel advantage, efficiency and added value obtained from effort processing of tobacco asepian countryside of Jonasari of subdistrict of trucuk of regency klaten Method used in this reasearch method survey, and determination of area sampel use the method of purposive sampling. Where election a group of subjeck based for characteristic or nature of certain which fooked into have in respect of clinging very hand in glove with the characteristic or nature of known population previously From advantage result of is effort processing of tobacco got advantage equal to Rp 27.007.819.41, efficiency equal to 1.22 and added value equal to 2,03.Keyword: Advantage, efficiency, added value